THE ROLE OF EMOTIONAL INTELLIGENCE IN LEADERSHIP: UNDERSTANDING PSYCHOLOGICAL FOUNDATIONS - Zahidah Jan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Emotional intelligence (EI) plays a pivotal role in effective leadership, enabling leaders to manage their emotions, understand others, and navigate complex social environments. This paper examines the psychological foundations of emotional intelligence, exploring its components self-awareness, self-regulation, motivation, empathy, and social skills and how these contribute to leadership effectiveness. By integrating insights from cognitive psychology, social intelligence theory, and neuroscience, the paper highlights how EI enhances decision-making, conflict resolution, communication, and motivation. The research underscores the importance of emotional intelligence in leadership development and organizational success, demonstrating that EI is essential for leaders to adapt, inspire, and drive positive change within their teams and organizations.